2012
DOI: 10.1128/jcm.05756-11
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Efficient Ziehl-Neelsen Stain: Identifying De Novo Intracellular Mycobacterium tuberculosis and Improving Detection of Extracellular M. tuberculosis in Cerebrospinal Fluid

Abstract: Tuberculous meningitis leads to a devastating outcome, and early diagnosis and rapid chemotherapy are vital to reduce morbidity and mortality. Since Mycobacterium tuberculosis is a kind of cytozoic pathogen and its numbers are very few in cerebrospinal fluid, detecting M. tuberculosis in cerebrospinal fluid from tuberculous meningitis patients is still a challenge for clinicians. Ziehl-Neelsen stain, the current feasible microbiological method for the diagnosis of tuberculosis, often needs a large amount of ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
2
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(83 citation statements)
references
References 30 publications
1
73
2
7
Order By: Relevance
“…The MZN stain was performed on all CSF specimens as described previously (9). In brief, 0.5 ml of CSF was loaded into a cytospin chamber with poly-Llysine-coated slides and centrifuged at 100 3 g for 5 minutes.…”
Section: Mzn Stainingmentioning
confidence: 99%
See 1 more Smart Citation
“…The MZN stain was performed on all CSF specimens as described previously (9). In brief, 0.5 ml of CSF was loaded into a cytospin chamber with poly-Llysine-coated slides and centrifuged at 100 3 g for 5 minutes.…”
Section: Mzn Stainingmentioning
confidence: 99%
“…The first is based on the hypothesis that intracellular M. tuberculosis may be missed by conventional ZN stain and their detection may be enhanced by improving the presentation of cells on the slide and increasing the permeability of the cells to the stain (modified ZN [MZN] stain). A proof-of-concept study found it revealed AFB by microscopy in 48 of 48 CSF specimens taken from 29 patients treated for TBM as opposed to 8 of 48 positive by conventional ZN stain (9). The second test is based on the premise that the CSF white cells, particularly professional phagocytic cells, of patients with TBM may contain concentrations of M. tuberculosis-specific antigens, in particular, early secreted antigen target (ESAT)-6.…”
mentioning
confidence: 99%
“…Prinsip dari Pewarnaan ZN adalah dinding bakteri yang tahan asam mempunyai lapisan lilin dan lemak yang sukar ditembus pengecatan, oleh karena pengaruh fenol dan pemanasan maka lapisan lilin dan lemak itu dapat ditembus cat karbol fuchsin. [4] Pada waktu pencucian dengan asam alkohol warna fuchsin tidak dilepas, Sedangkan pada bakteri tidak tahan asam akan luntur dan mengambil warna biru dari Metilen blue. Dalam metode pewarnaan ZN terdapat beberapa kekurangan yang akan mempengaruhi kesalahan pembacaan (negatif palsu), adanya artefak (sediaan kotor,endapan/Kristal reagen), sehingga dapat mempengaruhi pembacaan mikroskop.…”
Section: Pendahuluanunclassified
“…Dalam metode pewarnaan ZN terdapat beberapa kekurangan yang akan mempengaruhi kesalahan pembacaan (negatif palsu), adanya artefak (sediaan kotor,endapan/Kristal reagen), sehingga dapat mempengaruhi pembacaan mikroskop. [4,5] Penggunaan garam salmiak 10% pada sputum yang disentrifugasi 3000 rpm selama 15 menit, hasil penelitian menunjukkan bahwa penggunaan garam salmiak 10% dengan sentrifugasi dapat meningkatkan penemuan jumlah BTA, Sediaan yang dibuat secara langsung dengan jumlah BTA yang sedikit akan menyebabkan penyebaran tidak merata, hal ini dapat menyebabkan negatif palsu, sentrifugasi dilakukan untuk mengumpulkan BTA pada endapan, sehingga apabila endapan diambil dan dibuat sediaan akan diperoleh jumlah BTA yang lebih banyak [6]. Terdapat pada penelitian lain pada pemeriksaan BTA dengan mikroskopis menggunakan sentrifugasi lebih baik dengan hasil yang signifikan dari pada metode langsung.…”
Section: Pendahuluanunclassified
“…[3] Using the new acid-fast stain method of The Fourth Military Medical University, the positivity rate of CSF smear can be above 90%, enabling early diagnosis of tubercular meningitis. [4] Identifying the pathogens underlying cases of viral meningitis, weakly pathogenic bacterial meningitis, and parasitic meningitis is also difficult. For these reasons, the misdiagnosis rate in early meningitis is very high.…”
Section: Analysis Of the Misdiagnosis Rate Of Infectious Meningitismentioning
confidence: 99%